Amyloid formation: functional friend or fearful foe?. (6th May 2016) - Bergman, P.; Roan, N. R.; Römling, U.; Bevins, C. L.; Münch, J.
Abstract: Amyloid formation has been most studied in the context of neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease, as well as in amyloidosis. However, it is becoming increasingly clear that amyloid is also present in the healthy setting; for example nontoxic amyloid formation is important for melanin synthesis and in innate immunity. Furthermore, bacteria have mechanisms to produce functional amyloid structures with important roles in bacterial physiology and interaction with host cells. Here, we will discuss some novel aspects of fibril‐forming proteins in humans and bacteria. First, the amyloid‐forming properties of the antimicrobial peptide human defensin 6 (HD6) will be considered. Intriguingly, unlike other antimicrobial peptides, HD6 does not kill bacteria. However, recent data show that HD6 can form amyloid structures at the gut mucosa with strong affinity for bacterial surfaces. These so‐called nanonets block bacterial invasion by entangling the bacteria in net‐like structures. Next, the role of functional amyloid fibrils in human semen will be discussed. These fibrils were discovered through their property to enhance HIV infection but they may also have other yet unknown functions. Finally, the role of amyloid formation in bacteria will be reviewed. The recent finding that bacteria can make amyloid in a controlled fashion without toxic effects is of particular interest and may have implications for human disease. The role of amyloid in health and disease is beginning to be unravelled, and here, we will review some of the most recent findings in this exciting area. Abstract : Content List – Read more articles from the symposium: Amyloid ‐ a multifaceted player in human health and disease.